A State of Art Review on The New Innovations and Research in Education - Ramakant Sharma; Mayank Sharma (AG Volumes, 2022)
In a knowledge-based society, the technology functions as a tool for enlightenment and continually investigating the possibilities for innovation to redesign the way education has historically been distributed. Today the whole education system is developing more around the digital world and so the time has come to grasp the necessity to apply efficient solutions to make this system more optimal. Technology has swiftly revolutionized every part of the society, such as the education business. Today pupils grow up with the “internet-connected technologies” at home as well as in the school, which affects the way they study. Future education technique will alter learning by offering instructors and students a range of new tools to engage with such as digital platforms, virtual reality, e-learning, immersive learning etc. This paper presents a comprehensive survey on the ongoing innovations and research in the field of education that will shape its future.